2020
DOI: 10.1186/s40814-020-00703-0
|View full text |Cite|
|
Sign up to set email alerts
|

A randomised controlled feasibility study of interpersonal art psychotherapy for the treatment of aggression in people with intellectual disabilities in secure care

Abstract: Background Rates of aggression in inpatient secure care are higher than in other psychiatric inpatient settings. People with intellectual disabilities in secure care require adapted psychological treatments. Interpersonal art psychotherapy incorporates the use of creative art making approaches by participants, thus reducing sole reliance upon verbal interactions during psychotherapy for people who may have communication difficulties. During interpersonal art psychotherapy, participants are indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The proposed developing intervention is based on previous effectively established and implemented intervention models, including cognitive behavior therapy (CBT), parent-child interaction therapy, attachment-based therapy, social skills training (SST), and psychoeducational elements, which target self-efficacy and management of mental health and conduct problems tailored around goal-oriented approaches. SST and CBT group-based interventions are particularly effective in young people with autism [ 10 ]. Elements from these well-established approaches will contribute to behavior change in young people in secure care via upskilling them and building a goal-oriented approach toward their discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed developing intervention is based on previous effectively established and implemented intervention models, including cognitive behavior therapy (CBT), parent-child interaction therapy, attachment-based therapy, social skills training (SST), and psychoeducational elements, which target self-efficacy and management of mental health and conduct problems tailored around goal-oriented approaches. SST and CBT group-based interventions are particularly effective in young people with autism [ 10 ]. Elements from these well-established approaches will contribute to behavior change in young people in secure care via upskilling them and building a goal-oriented approach toward their discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The perspective of professionals is important, as their attitudes and choices impact the quality of care (Pelleboer-Gunnink et al 2021). Hackett et al (2020) used the therapist version of the WAI-SF within a small exploratory study that sought to determine the feasibility of interpersonal art therapy for adults with mild IDs and anger problems, without further exploring the psychometric properties of this measurement.…”
mentioning
confidence: 99%
“…Hackett et al . ( 2020 ) used the therapist version of the WAI‐SF within a small exploratory study that sought to determine the feasibility of interpersonal art therapy for adults with mild IDs and anger problems, without further exploring the psychometric properties of this measurement.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in author 3’s last name. The correct last name should be “Aafjes-van Doorn” instead of Aafjes-van Doorm.…”
mentioning
confidence: 99%